ANALISIS CUSTOMER SATISFACTION MOTOR MEREK YAMAHA NMAX DI PONTIANAK TIMUR - Hijrah Wahyudi; Mardiyati Mardiyati (Jurnal Ekonomi STIEP, 2021)
This study aims to determine customer satisfaction with Yamaha NMAX motorcycles by using serviceability , price, warranty, bonus, and promotion variables. This research uses survey method and purposive sampling technique to 100 respondents in East Pontianak . The results of the regression analysis show that five independent variables simultaneously have a significant effect on customer satisfaction for Yamaha NMAX motorcycles in east Pontianak. The magnitude of the influence of the five independent variables on customer satisfaction with Yamaha NMAX simultaneously is 88,40% while the remaining 11,6% is influenced by other factors not examined in this study.